The Anthroposphere and Mining Activities - Perny, Koji Cristobal Ishimi; Sobczyk, Wiktoria (Journal of Education, Technology and Computer Science, 2020)
This article presents some aspects of goals and tasks of sustainable development. The theoretical preliminary analysis of environmental hazards in mining in the anthroposphere is described. The publication is focused on influencing people and environmental elements that affect people’s living conditions.